2017
DOI: 10.1136/bmjopen-2017-017835
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal influenza vaccine effectiveness against laboratory-confirmed influenza in 2015–2016: a hospital-based test-negative casecontrol study in Lithuania

Abstract: ObjectiveA case–control study was conducted to assess seasonal influenza vaccine effectiveness (SIVE) during the 2015–2016 influenza season.MethodsA study was performed in three departments in Lithuania between 1 December 2015 and 1 May 2016. Data on demographic and clinical characteristics including influenza vaccination status were collected from the patients recommended to receive the seasonal influenza vaccine. Influenza virus infection was confirmed by multiplex reverse transcription polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Conversely, we found a significant 44.6% VE against this virus, which remains similar to previous seasons (Belongia et al 2016;Darvishian et al 2017; Table 4 Absolute numbers of influenza cases and non-cases among vaccinated and unvaccinated ILI patients. Jackson et al 2017;Kuliese et al 2017). Thus, due to the high circulation of the influenza A(H1N1)pdm09 virus in Mexico, our results may provide more accurate VE estimates that may serve as a global reference about protective effectiveness of the 2016/17 influenza vaccines against this virus.…”
Section: Discussionmentioning
confidence: 87%
“…Conversely, we found a significant 44.6% VE against this virus, which remains similar to previous seasons (Belongia et al 2016;Darvishian et al 2017; Table 4 Absolute numbers of influenza cases and non-cases among vaccinated and unvaccinated ILI patients. Jackson et al 2017;Kuliese et al 2017). Thus, due to the high circulation of the influenza A(H1N1)pdm09 virus in Mexico, our results may provide more accurate VE estimates that may serve as a global reference about protective effectiveness of the 2016/17 influenza vaccines against this virus.…”
Section: Discussionmentioning
confidence: 87%
“…In our cases, the overall mortality rate was 6%, while the mortality rate was 66% for those who needed intensive care. Kuliese et al have reported the mortality rate as follows 5.6% [7] . In Korea, a mortality rate of 1.3% in adult patients hospitalized with influenza and a mortality rate of 27% in the ICU have been reported [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Comorbid diseases associated with old age are also factors that increase the risk of hospitalization due to influenza. Kuliese et al reported 72 laboratory confirmed influenza positive patients, of whom 87% had at least one comorbid disease and 47% had cardiovascular disease [7] . The most common comorbidities in our study were COPD (29%) and chronic heart disease (19%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Influenza-positive samples were subtyped to influenza A(H1N1)pdm09, influenza A(H3N2), influenza B/Yamagata, or influenza B/Victoria. The laboratory analysis, in more detail, is described elsewhere [ 12 ].…”
Section: Methodsmentioning
confidence: 99%